Production performance and management practices of Pugal sheep in the home tract - Dass, Gopal (The Indian Journal of Animal Sciences, 2007)
A survey was conducted to study the performance and husbandry practices of Pugal sheep in its home tract. Data were recorded on management practices, body measurements, body weights, wool production and reproduction. Results indicated that animals were maintained under extensive management with at least 10 h grazing daily. Breeding rams were selected without giving due consideration to breed; and breeding and lambing took place throughout the year. Three-times shearing in a year, vaccination and routine treatment were also practised. The overall least squares means of body measurements of adults, viz. body length, height, chest girth, ear length and tail length were 61.59±0.31, 61.76±0.17, 71.83±0.20, 9.48+.0.11 and 17.70±0.22 cm, respectively. Body weights at birth, 3, 6, 12 months and adult weights were 2.62±0.01, 17.70±0.05, 23.67±0.09, 29.62±0.26 and 39.04±0.26 kg, respectively. Least squares means for greasy fleece weights in first, second, third and total annual clips were 558, 513, 549 and 1618 g, respectively. Body weights and greasy fleece weights differed significantly (P&lt0.01) in the two sexes, males gained higher weights at all stages and produced heavier fleece in all the clips. The body weights of this breed were found quite comparable with Magra breed, which had the same breeding tract. Wool quality parameters indicated the suitability of wool for medium quality carpet manufacture. Age at first oestrus, age at first lambing, lambing percentage and lambing interval were 10.15±0.05 months, 15.47±.07 months, 98.12±4.25% and 283.13±0.95 days, respectively.